PENGARUH KEJADIAN WASTE DENGAN PENDEKATAN LEAN HOSPITAL TERHADAP PROFITABILITAS INSTALASI FARMASI MELALUI PENGENDALIAN PRODUKSI DI ERA BPJS - Nadhir, Yany Khoirurakhmawati; Fitriasari, Nikmah; Rahmatika, Fiella; Luciana, Dya; Purba, Iqbal Syaidul (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
Background: Change in claim payment of Healthcare and Social Security Agency (BPJS) requires hospitals to improve the management using lean hospital approach. Hospital pharmacy installation attempts to reduce waste and control production costs to increase profitability. Objective: The study aimed to know the effect of waste events with lean hospital approach on the profitability of hospital pharmacy installation in XX Hospital through production costs control. Method: The study used quantitative observational research design with cross sectional study. The research was carried at XX Hospital in July-August 2018. The number of respondents was 36 obtained from total sampling technique.Then, Partial Least Square (PLS) was applied to analyze the obtained data. Results: The PLS results showed that waste had a direct negative effect on production costs control (0.727) while it had positive direct effect on profitability (3.757). Production costs control had positive direct effect on profitability (19.422). Waste did not significantly affect profitability through production costs control (-0.726). Conclusion: It can be concluded that waste decrease can increase production costs control. Effective and efficient production costs control can increase profitability. The more waste decrease results in the higher profitability.Â